Female Sexuality: An Enigma - Daniluk, Judith (Canadian Journal of Counselling and Psychotherapy, 2011)
In North American society, constructions of sexuality, manifested in terms of gender appropriate sensing, feeling, knowing and experiencing, have occurred within a social context in which language, culture and behaviour interact to reinforce male power and privilege. To date, women have not played a major role in the construction of our own sexual paradigms. Against the backdrop of these patriarchal paradigms of female sexual expression and experience, the difficulties of female clients are discussed. Critical counseling concerns are addressed in terms of contextual realities, the construction of new paradigms, life cycle issues and the impact of sexual violence.